(untitled) (The Journal of Nuwakot Adarsha Multiple Campus, 2024)
Background: Education is essential for individuals as it provides skills and opportunities for livelihood. The privatization of education, which was promoted by the UK government in 1979. In Nepal, public and private schools differ in academic reputation, with private schools often perceived as having higher standards. Methods: This study aimed to compare parents’ perceptions of school quality based on whether their children attend public or private schools. A survey of 128 publics and private school’s students’ parents was conducted using a cross-sectional design. Results: The study found that parents of children in private schools had a more favorable view of school quality than parents of children in public schools. This could result in public schools losing high-achieving students to private schools. Factors such as land ownership (P=0.018), owning an ox at home (P=0.011), having a television (P=0.030), and receiving scholarships, textbook prizes, and free exam fees from the school (P<0.001) were statistically significant. Conclusions: Public schools play a vital role in providing quality education, but their standards have been declining due to neglect. Despite having trained teachers and good facilities, parents are increasingly choosing private schools. The government invests in all sectors of public schools, but there is a need for a plan to improve their image.